Knowledge of Chlamydia trachomatis among men and women approached to participate in community-based screening, Scotland, UK - Hart Graham J; Lorimer Karen (BMC, 2010)
Abstract Background Poor awareness and knowledge of Chlamydia trachomatis could be a barrier to uptake of screening. This study aimed to determine the level of awareness and knowledge of chlamydia among young people who were being approached in a variety of community settings and offered opportunistic screening. Methods Men and women aged 16-24 years were approached in education, health and fitness, and workplace settings and invited to complete a self-administered questionnaire then provide a urine sample for chlamydia testing. Follow-up semi-structured interviews with 24 respondents were carried out after test results were received. Results 363 questionnaires were completed (43.5% from men). Whilst awareness of chlamydia was high, knowledge decreased as questions became increasingly focussed so that around half of respondents were unaware of the asymptomatic nature of chlamydia infections. Men's knowledge of symptoms was consistently lower than women's, with most men failing to identify unusual discharge as a symptom in men (men 58.3%, female 45.8%, p = 0.019); fewer men knew unusual discharge was a symptom among women (men 65.3% female 21.4%, p < 0.001). The asymptomatic nature of the infection resonated with respondents and was the commonest piece of information they picked up from their participation in the study. Conclusions Despite scientific gains in understanding chlamydia infection, public understanding remains limited. Greater efforts are required to translate scientific evidence to the public. An improvement in knowledge may maximise gains from interventions to improve detection.